THE EFFORTS OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN INSTILLING VALUES MORALS IN STUDENTS AT STATE VOCATIONAL SCHOOLS 1 TEBING TINGGI - Zailani Zailani; Tia Aulia (Jurnal Scientia, 2022)
The teacher is a figure who is expected to be able to provide enlightenment and guidance in the behavior of children. Included in the moral development of students, so that students can distinguish what is good and what is bad according to reason and norms that exist in the environment where students are. Moral development must start from the basic level, so that students have a strong foundation in daily behavior. This study took SMK Negeri 1 Tebing Tinggi as the object of research. As for the results of the study, there were still many students of SMK Negeri 1 Tebing Tinggi who were not good at reading the Qur'an. Efforts are made by Islamic Religious Education Teachers by: (1) Cultivating morals in students, (2) praying dhuha and dzuhur in congregation and (3) learning to read the Qur'an and memorize daily prayers. So that the efforts made by Islamic Religious Education Teachers can be said to be less successful, it can be seen that 30% of students have not been able to read the Qur'an.